The semantic components of armenian toponyms - Dilbaryan, Narine (Bulletin of Yerevan University B: Philology, 2021)
The proper  names given to the geographical units are very often in a direct relation with the natural characteristics of the external world realities and form thematic groups on the basis of this or that overlap of the semantic characteristics, which directly expresses the interconnection between the process of naming of the given geographical unit. Based on internal and external characteristics of the geographical units and the residences in toponymy it is accepted to underline the following 9 semes: 1) «drawing, the form of the object» the following sememe is expressed in various substantivized adjectives, some of them turn into toponyms with zero morpheme in Armenian, with suffixation, composition and in word-formation process - տափ, (plain) հարթ(flat), զառիվայր (ramp), ծուռ (hooked), թեք (slanting), 2) «the peculiarities of water flaw »- արագ (swift), վարար (turbulent), խաղաղ (peaceful) 3) «'temperature-related peculiarities» - սառն(cold), ջերմ (warm), թեժ (hot), գոլ (humid),  4) «peculiarities of soil layers» -հողե (soil), կավային(clay), տիղմային (sludge), ավազե (sand), ճահճային(swamp), քարե (stone), 5) «smell, odour» անուշ (nice), գարշ(smelly), 6) «flavour sensation»-- քաղցր (sweet), թթու(sour), դառն (bitter), 7) «colour, tint» - սև (black), սպիտակ(white), կարմիր(red), ոսկի(gold), կապույտ(blue), կանաչ(green), 8) «spiritual and religious qualities» - divine, devilish, holy, and 9) «moral and aesthetic qualities» - evil, kind, proud etc. In the Armenian toponyms the majority form the ones with the 4 following semes «drawing, the form of the object», «'the peculiarities of the soil layer», «colour», and «spiritual and religious qualities». For example, Տափեր, Տափերական, Հարթք, Հարթենք, Հարթագոմեր, Հարթագյուղ, Քարեր-Քարինք Քարընկեց, Կարմրաշեն, Կարմրաթառ, Կարմրամորուս, Բարեբեր, Չարաբերդ etc.
Keywords: toponym; word formation; compounding; word combination; construct definition-definable; semiotics; seme; internal and external qualities